Unconventional methods, techniques, and equipment for strength and conditioning in combat sports - Santana, J. C.; Fukuda, D. H. (Strength and Conditioning Journal, 2011)
Throughout the last decade, various forms of training have come to the forefront of fitness, strength, and conditioning. Exercises from strongman competitions, functional training, and other genres have been combined into a unique style of training. This style of training offers a diverse collection of methods that, if properly applied, can serve as an excellent tool for personal trainers and strength and conditioning coaches to apply with athletes.